SISTEM PENUNJANG KEPUTUSAN PEMILIHAN NOTEBOOK DENGAN MENGGUNAKAN METODE TOPSIS - Heru Purwanto (LPPM Nusa Mandiri, 2017)
Technology developments so rapidly that thinking about a lot of feature and the choice of models on offer. A notebook is a piece of technology equipment that has been chosen to assist in the execution of tasks from school or duties of the office. The form is simple and practical, and comes with some interesting features make Notebook users increasingly more freely given the freedom to be more creative in their ideas of creative -ide owned. Currently, there are some interesting deals offered by many electronics companies primarily engaged in the business of selling Notebook. Notebook many choices often makes prospective consumers confused to choose one of the many options offered. The author intends to give recommendations to consumers about the election Notebook. In the selection of twelve criteria, namely, the design includes colors, models and extrinsic value. The next criteria are memory, connectors, data transfer and performance criteria being part of the supporting technology. Display and Audio is the next criteria include graphics, sound, and Pixel. The size and position of choice for media input criteria. There are four alternatives used in sorting Notebook, they are Toshiba, Asus, Samsung and HP Method used in the study is Technic for Order Preference by Similarity to Ideal Solution (TOPSIS). With this method is expected to assist in decision making Notebook election. Based on the data obtained through the questionnaire and performed the data processing can be seen from the four alternatives the maximum to meet the set criteria is Toshiba with a value of 0.569